2018
DOI: 10.1159/000489605
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Thromboelastometry for Adult Living Donor Liver Transplant Recipients with a Tendency to Hypercoagulability: A Prospective Observational Cohort Study

Abstract: Background: Hypercoagulability can lead to serious thromboembolic events. The aim of this study was to assess the perioperative coagulation status in liver transplant recipients with a tendency to hypercoagulability. Methods: In a prospective observational study (South African Cochrane Registry 201405000814129), 151 potential liver transplant recipients were screened for thrombophilic factors from October 2014 to June 2017, and 57 potential recipients fulfilled the inclusion criterion of presenting two or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 58 publications
0
21
0
2
Order By: Relevance
“…Both these parameters reflect the strength of the blood clot and depend on platelet count and function and the integrity of the fibrin network (fibrin levels and polymerization, factor XIII). 41,45 High MA and MCF values have been strongly associated with an increased risk of thromboembolic complications in hospitalized patients [46][47][48][49] ; however, these data are derived from non-COVID-19 studies. A clinical consequence of hypercoagulability in severely ill COVID-19 patients may be the frequent occurrence of venous and arterial thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…Both these parameters reflect the strength of the blood clot and depend on platelet count and function and the integrity of the fibrin network (fibrin levels and polymerization, factor XIII). 41,45 High MA and MCF values have been strongly associated with an increased risk of thromboembolic complications in hospitalized patients [46][47][48][49] ; however, these data are derived from non-COVID-19 studies. A clinical consequence of hypercoagulability in severely ill COVID-19 patients may be the frequent occurrence of venous and arterial thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…tibodies) and patients with hepatocellular or cholangiocellular carcinoma [138][139][140][141]. Again, this emphasizes the need for a correct dose-adjustment and that overtreatment-also with fibrinogen-should strictly be avoided.…”
Section: Görlinger Et Almentioning
confidence: 99%
“…Several studies prior to the COVID-19 pandemic demonstrated that an EXTEM or INTEM MCF of > 68 mm (A10 > 61.5 mm) is a strong indicator of hypercoagulability and predictor of thrombosis [ 17 , 18 ]. A FIBTEM MCF value of > 25 mm is associated with a five-fold increased risk of developing thrombosis in cirrhotic patients with hepatocellular carcinoma [ 19 , 20 ]. Hypercoagulability in COVID-19 patients was assessed by rotational thromboelastometry, which is used as a diagnostic tool [ 21 , 22 ].…”
Section: Rotational Thromboelastometrymentioning
confidence: 99%